2016
DOI: 10.1128/jvi.01051-16
|View full text |Cite
|
Sign up to set email alerts
|

Acute Liver Damage Associated with Innate Immune Activation in a Small Nonhuman Primate Model of Hepacivirus Infection

Abstract: Despite its importance in shaping adaptive immune responses, viral clearance, and immune-based inflammation, tissue-specific innate immunity remains poorly characterized for hepatitis C virus (HCV) infection due to the lack of access to acutely infected tissues. In this study, we evaluated the impact of natural killer (NK) cells and myeloid (mDCs) and plasmacytoid (pDCs) dendritic cells on control of virus replication and virus-induced pathology caused by another, more rapidly resolving hepacivirus, GB virus B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(41 citation statements)
references
References 61 publications
3
38
0
Order By: Relevance
“…Our previous study of acute and chronic GBV-B infection suggested immune activation induces significant acute liver pathology in marmosets (Manickam et al, 2016). Strikingly, in this reinfection study, pathological manifestations were observed in the livers of re-infected animals despite only very low levels of virus replication.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Our previous study of acute and chronic GBV-B infection suggested immune activation induces significant acute liver pathology in marmosets (Manickam et al, 2016). Strikingly, in this reinfection study, pathological manifestations were observed in the livers of re-infected animals despite only very low levels of virus replication.…”
Section: Resultsmentioning
confidence: 98%
“…Following primary infection, all animals rapidly developed viremia with variable clearance (Fig 1) (Manickam et al, 2016). Prior to re-challenge, all animals were confirmed to be aviremic on day 300 relative to primary infection (heretofore day 0 of re-infection) (Fig 1A).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations